Gamification of Neuropsychological Tools as a Multi-Sensory Approach to Education. Stroop's Paradigm - Gkintoni, Evgenia; Halkiopoulos, Constantinos; Antonopoulou, Hera; Petropoulos, Nikos (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The Stroop test is a neuropsychological assessment that is worldwide recognized for its sensitivity and reliability in assessing frontal activation and executive function control. The Stroop test was conducted in this research effort using the Unity machine in a virtual test with the identical application approach and outcome measurement as in the physical test. The new visual "ustroop" test was conducted to a large enough sample of persons to allow comparisons to the initial test. Subsequently, more game scenarios in the form of a play script were added to evaluate the player's reaction to color, brand name, and words. To summarize, neuropsychological evaluation techniques can be used to promote and evaluate visual gaming, and the current project's findings can be developed upon. Though, scientific fields such as cognitive neuroscience, neuropsychological assessment tools, and gamification techniques can effectively increase learning and cognitive function through continual exercise and can be an asset in the educational process.